Pregnancy-associated venous thromboembolism in combined heterozygous factor V Leiden and prothrombin G20210A mutations - Couto, Egle (2005)
CONTEXT: Pregnancy and puerperium raise the risk of thromboembolic events, and these risks are increased in women who are carriers of throm- bophilia factors. Prothrombin (FII) G20210A and factor V Leiden heterozygous mutations are associated with moderate risk of thrombosis. The association of these thrombophilic conditions is very rare in pregnancy, and the real risk of thrombosis is unknown. CASE REPORT: We describe a case of a preg- nant woman who was found to be carrier of heterozygous factor V Leiden and prothrombin (FII) G20210A mutations. Five years before preg- nancy she had had an episode of extensive deep venous thrombosis in the ileofemoral region, while using hormonal contraceptives. Anticardiolipin antibody (ACA), lupus anticoagulant and defi- ciencies of protein C, protein S and antithrombin III were evaluated by means of enzyme-linked immunosorbent assay (ELISA), dilute Russell Viper Venom time (dRVVT), coagulometric and chromogenic methods. Deoxyribonucleic acid (DNA) was amplified using the polymerase chain reaction (PCR) to study the factor V Leiden and G20210A mutations in the prothrombin gene and C677T mutation in the methylene tetrahydrofolate reductase (MTHFR) gene. In the sixth week of her first pregnancy, she developed another episode of deep venous thrombosis in the femoropopliteal veins of the right leg. She was treated with low-molecular weight heparin (nadroparin) until parturition (0.3 ml or 2,850 UI/day). The preg- nancy evolved without any significant obstetric morbidity. The patient delivered a healthy baby by cesarean section. During the puerperium, she used prophylactic doses of nadroparin for (0.3 ml or 2,850 UI/day) six weeks and had no complications. We suggest that women who have an association of thrombophilia factors and a prior episode of venous thromboembolism must have antepartum anticoagulation management using unfractioned or low-molecular weight heparin and postpartum management using low-molecular weight heparin or oral anticoagulants. Antico- agulation is recommended during pregnancy because the real magnitude of the risk of major and life-threatening thromboembolic events in these women is unknown.